Evaluation and Credentialing in Digital Music Communities Benefits and Challenges for Learning and Assessment - Suhr, H. Cecilia (The MIT Press, 2014)
An examination of the use of digital badges as a reward for both casual online music evaluators and professional musicians.Professional and amateur musicians alike use social media as a platform for showcasing and promoting their music. Social media evaluation practices-rating, ranking, voting, "liking," and "friending" by ordinary users, peers, and critics-have become essential promotional tools for musicians. In this report, H. Cecilia Suhr examines one recent development in online music evaluation: the use of digital badges to aid in assessment and evaluation. Digital badges have emerged in recent years as a potential credentialing method in informal learning environments. Suhr explores online music communities' use of digital badges as a reward for both casual music evaluators and musicians.Suhr examines the intersection of evaluation and gamification in Spotify's "Hit or Not" game, in which players assess a song's hit potential and receive digital badges as rewards, and considers the implications of turning music evaluation into a game. She then explores in detail the development of peer and professional critics on Indaba Music, a cloud-based collaboration platform where musicians earn badges through participating in contests. Suhr considers the emerging challenges and shortcomings of contest-based virtual communities and the value of badges, as perceived by Indaba musicians. She investigates to what extent digital badges can effectively represent and credit musicians' accomplishments and merits; describes the challenges, benefits, and shortcomings of digital badges as an evaluation mechanism; and compares the use of digital badges in assessing creativity to their use in learning and credentialing institutions.